Synthesis of d-Fagomine and Its Seven- and Eight-Membered Higher-Ring Analogues, and the Formal Synthesis of (+)-Australine from l-Xylose-Derived Chiron - Das, Pintu; Ajay, Sama; Shaw, Arun K. (Synthesis, 2016)
The synthesis of d-fagomine and its seven- and eight-membered higher-ring analogues from commercially available l-xylose is reported. The syntheses involve elaboration of a common alkenol precursor obtained from l-xylose-derived hemiacetal. The key steps in the syntheses are intramolecular reductive amination and ring-closing metathesis for the synthesis of d-fagomine and seven-/eight-membered iminosugar, respectively. We have also extended our synthetic strategy for the formal synthesis of (+)-australine using zinc-mediated fragmentation reaction and ring-closing metathesis as key steps.
Keywords: d-fagomine; aminocyclitols; metathesis; (+)-australine; reductive amination